Kritobulos of Imbros: Learned historian, Ottoman raya and Byzantine patriot - Reinsch-Roderich Diether (Zbornik Radova Vizantološkog Instituta, 2003)
Kritobulos of Imbros, the author of a historical work covering the period from 1451 to 1467, describes the deeds of the Sultan Mehmed Fatih. The work written between 1465 and 1467 is an autograph of the author. Apart from a knowledge of literature (Thucydides), one can discern in this work a definite interest in medicine. K. was sultan's governor of Imbros for almost ten years. At the same time he was a patriot in the sense that he expressed solidarity with the unfortunate inhabitants of Constantinople.